Kampanye Sosial UEFA dan Implikasinya Terhadap Ekosistem Olahraga Sepak Bola di Eropa - Silitonga, Immanuel Josua H.; Nugrahani, Henny Saptatia Drajati (Jayapangus Press, 2025)
In the context of football, acts of discrimination represent one of the biggest obstacles to creating an inclusive environment that ensures equality and fairness for all stakeholders in the sport. As an effort to anticipate discriminatory actions, UEFA employs social campaigns to promote inclusive values and norms within the European football ecosystem. This study aims to explore the reasons why UEFA has used campaigns between 2019 and 2023 as a preventive measure against discrimination in European football. Using the concept of social inclusion in sports and a qualitative approach, the research reveals that UEFA utilizes campaigns to address various structural issues that give rise to discrimination in European football. Furthermore, these campaigns also have implications for the football ecosystem by demonstrating the internalization of inclusive norms, concretely implemented through policies, programs, and regulations. These efforts are analyzed in the context of two countries chosen to represent the European football ecosystem: England and Spain.